Hydrolysis preparation of the compact TiO2 layer using metastable TiCl4 isopropanol/water solution for inorganic–organic hybrid heterojunction perovskite solar cells*Project supported by the National Natural Science Foundation of China (Nos. 51472071, 51272061, 51072043), and the National Basic Research Program of China (No. 2011CBA00700). (July 2015) - Dai 代, Xiaoyan 晓艳; Shi 史, Chengwu 成武; Zhang 张, Yanru 艳茹; Wu 吴, Ni 妮
Abstract: A hydrolysis process was applied to prepare the compact TiO2 layer using the fresh metastable TiCl4 isopropanol/water solution as the precursor solution for the preparation of the inorganic–organic hybrid heterojunction perovskite solar cells. The optimal compact TiO2 layer prepared from the aqueous solution of 2 mol/L TiCl4 diluted in isopropanol at 1 : 3 by volume as precursor solution was uniform and with a film thickness of 126 nm. The corresponding perovskite solar cell gave a photovoltaic conversion efficiency of 10.61%.